Bahaya gula bagi anak-anak: Mengapa orang tua harus mengawasi konsumsi gula pada anak - yanah, muda (Maliki Interdisciplinary Journal, 2025)
Kids love sweet foods like candy, chocolate, and sweetened drinks. Consuming excessive sugar from an early age can have an impact on body health such as tooth decay, obesity, and diabetes. The Indonesian Doctors Association (IDAI) shows a fairly high increase in children with diabetes. For children, sweet foods such as candy, chocolate, ice cream and sweetened drinks are seen as mandatory foods for them every day. But not many children do not consume these foods but rather the habits given by their parents.It is therefore important for parents to keep an eye on and understand what goes into their children's bodies. This article aims to educate all levels, including parents, about the dangers of consuming excessive sugar for children, the impact of sugar on health, and monitoring strategies that parents can do.